Pengembangan Aplikasi Pendaftaran Online Layanan Pencatatan Sipil Berbasis Web Menggunakan PHP dan Basis Data MySQL (Studi Kasus: Dispendukcapil Kabupaten Malang) - Januari Siregar; Ismiarta Aknuranda; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Dispendcukcapil Malang Regency is conducting services that can help to speed up the process of publishing population documents. Based on the observations and interviews, the conventional service that curently being run, especially on the civil registration document which is marriage certificate issuance, found some problems, those are the uncertain of form inventory in the head village, the discovery of grafitty on the form, and consuming a lot of time for people who live far from the Dispenduk office. Based on these problem, so the aplication web-based of online registration for civil registration service are being developed to serve a online registration for people of Malang Regency. Development method used is waterfall method. For the model design used is a structured design model In impementation phase, used PHP programming language and some libraries such as Bootstrap, Jquery, and Java Script. In testing, validation test and compatibility test were performed. The result of this research is the registration of the civil document information system website. This information system is expected to help the public in conducting the process of the submission of the civil document